The Holistic Life-Crafting Model: a systematic literature review of meaning-making behaviors - van Zyl, Llewellyn E.; Custers, Noah C. M.; Dik, Bryan J.; van der Vaart, Leoni; Klibert, Jeff (Frontiers in Psychology, 2023)
Pursuing meaningful life experiences is vital for wellbeing and health. Crafting strategies, such as job crafting and work-life balance crafting, have been developed to create meaning in specific life domains. However, these strategies share common underlying behaviors that transcend specific contexts. Building on this understanding, we propose a comprehensive “holistic life crafting” approach that integrates overlapping behaviors from various crafting strategies. This study aims to clarify the theoretical conceptualization of life crafting by identifying common strategies and behaviors underlying different meaning-making crafting approaches. Through a systematic literature search of six databases between January and April 2022, we identified 16,479 published records. Using predefined inclusion-exclusion criteria, 51 records (reflecting five crafting approaches, resulting in 223 different crafting behaviors) remained. Through content analysis, we grouped these behaviors into seven broader crafting strategies, forming the “holistic life crafting” approach. Findings suggest that life-crafting is a holistic, continuous process of proactive meaning-making by intentionally balancing life demands with available resources and altering life's cognitive, environmental, interest, relational, skill, and task-related aspects to promote personal growth and wellbeing. The holistic approach encompasses cognitive, environmental, interest, relational, resources-demands, skill, and task crafting strategies. This framework provides a comprehensive understanding of how individuals can actively shape their lives to promote more meaningful life experiences across different domains.